(untitled) (Research, Society and Development, 2023)
Evaluated the intake and nutrient digestibility of diets containing cassava stem and foliage silage (CSFS) and concentrated. We used 20 crossbred goats, castrate, with average weight of 17kg, distributed in a completely randomized design for a period of 25 days. The proportions of total concentrate diets were 0, 20, 40 and 60%, made according to (NRC 2007). The digestibility coefficients were determined by total collection of feces. Data on intake and digestibility were evaluated by analysis of variance and regression using the program SISVAR (2005). The addition of concentrates to the diet did not affect (P>0.05) on intake (g/day, %BW, g/UTM) of DM, CP, OM and MM, where the EE were significant (P<0.05) showing a linear decrease, observing the same result for the NDF and ADF in %BW and g/UTM. The intakes (g/day, %BW and g/UTM) CNF showed an increasing linear effect (P<0.05). The digestibility coefficients were not significant (P>0.05) with the addition of concentrated diets. Nitrogen balance was similar (P>0.05) between diets spiked with concentrates.